Merleau-Ponty : de la ambigüedad a la hiperdialéctica - Franck, Juan F. (Sapientia, 2008)
The analysis of Merleau-Ponty’s thought, from his phenomenology of perception through his posthumous work, reveals that the author maintained his basic initial position unmodified. The ambiguity of sensitive perception, which worked as a critical element against empiricism and rationalism, evolves into a dialectical –hyperdialectical, in the author’s terms– in which subject and world are only dialectical moments of a unique reality called flesh. The article makes clear that such metaphysics is in no way required by the phenomenology of perception, but answers to an independent option. At the same time, it underlines several flaws both in the phenomenology of ambiguity and in hyperdialectics.